A mixed methods pilot feasibility study of the unified protocol group psychotherapy for early bipolar disorder - Magnus Johan Engen; Siv Hege Lyngstad; Erlend Eikenæs; Jon Vøllestad; Margrethe Collier Høegh; Trine Vik Lagerberg; Trine Vik Lagerberg; Sofie Ragnhild Aminoff (Frontiers in Psychiatry)
In this pilot study we explored the feasibility and acceptability of “The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders” (UP) in a group format for individuals with early bipolar disorder (BD). Using a mixed methods design we integrated quantitative assessments and qualitative interviews to examine the practical application of UP in a clinical setting with a focus on how participants experienced the treatment. Nine participants with BD diagnoses completed the 12-session group intervention with modules focusing on emotion regulation through skills in non-judgmental awareness, cognitive flexibility, and exposure strategies. Quantitative findings indicated significant improvements in affective lability, overall functioning, and well-being. Qualitative findings highlighted participants’ appreciation for the structured format and peer support from the group, which facilitated exploration of emotional experiences and skills practice. Participants reported particular benefit from non-judgmental awareness exercises, notably the “three-point check,” and valued the group’s role in reducing isolation and promoting shared learning. The study underscores UP’s potential adaptability for individuals with BD in a group format. Possible adjustments are discussed, such as strengthening the focus on affective symptoms as well as increasing session duration and customizing exposure exercises for BD-specific challenges. Overall, the UP group format shows promise as a feasible, acceptable, and potentially effective adjunct treatment for BD, with room for targeted refinements to optimize outcomes.